Social Cognition, Motivation, and Interaction How Do People Respond to Threats in Social Interactions? - Eva Jonas (Frontiers Research Topics, 2018)
f we want to understand people's responses to threats in social interactions we can distinguish between three levels of analysis:On a social level of analysis we can describe people's interpersonal behavior, on a cognitive level we can identify corresponding information processing mechanisms, and on a neural level we can specify neural systems, which underlie these processes.In this Research Topic we want to present research connecting these three levels of analysis and propose their functional interconnection in social interaction.We propose that threats in social interactions activate basic motivational processes, which manifest in neural processes related to behavioral inhibition vs. activation in a social situation. This shapes our attention to new information, and affects our cognitions about social identities, belief systems and worldviews. These changes in social cognition in turn affect people's behavior in social interactions and lead to corresponding reactions on behalf of the interaction partner. Thus, we assume that people's reactions to threat in interactions can be described as sequences of broader attentional processes resulting from basic motivational tendencies leading to specific social cognitions and subsequent behavior within social interactions. We can analyze this sequence in order to contribute to a better understanding of social interactions.The three levels of analyses (social, cognitive, neural) shed light on social interactions from different angles:On the social level we can analyze how the behaviors of the interaction partners mutually affect each other and how this is accompanied by specific cognitive, emotional and motivational processes. On the cognitive level we can analyze people's perception of a social situation leading to attentional and reasoning processes with regard to their interaction partner/s, which may be accompanied by certain emotional and motivational processes and determines the behavior towards the partner/s. Finally, we can focus on the neural mechanisms underlying cognitive, emotional, and motivational processes in social interactions.